Supporting Older People to Live Safely at Home – Findings from Thirteen Case Studies on Integrated Care Across Europe - Lette, Manon (Int J Integr Care, 2020)
INTRODUCTION: While many different factors can undermine older people’s ability to live safely at home, safety as an explicit aspect of integrated care for older people living at home is an underexplored topic in research. In the context of a European project on integrated care, this study aims to improve our understanding of how safety is addressed in integrated care practices across Europe. METHODS: This multiple case study included thirteen integrated care sites from seven European countries. The Framework Method guided content analyses of the case study reports. Activities were clustered into activities aimed at identifying and managing risks, or activities addressing specific risks related to older people’s functioning, behaviour, social environment, physical environment and health and social care receipt. RESULTS: Case studies included a broad range of activities addressing older people’s safety. Although care providers felt they sufficiently addressed safety issues, older people were often concerned and insecure about their safety. Attention to the practical and social aspects of safety was often insufficient. CONCLUSIONS AND DISCUSSION: Integrated care services across Europe address older people’s safety in many ways. Further integration of health and social care solutions is necessary to enhance older people’s perceptions of safety.